Parent training for autism spectrum disorder : improving the quality of life for children and their families - Johnson, Cynthia R. (Cynthia Rheney); Butter, Eric M.; Scahill, Lawrence (American Psychological Association, 2019)
"Children with autism spectrum disorder (ASD) present many challenges to their parents. Caring for children with ASD can be expensive, exhausting, and more burdensome than parenting children with other disabilities. One of the emerging empirically supported interventions available for helping parents and children with ASD is behavioral parent training (PT). This book focuses on behaviorally based PT as a treatment model for addressing disruptive behavior and skill deficits in children with ASD. The introduction section presents a brief overview of the book. The book comprises of 10 chapters. Chapter one provides a historical account and theoretical basis for the PT model. Chapter two reviews a range of assessment tools for diagnosis of ASD and pretreatment measurement as a starting point in the treatment planning process. Chapter three discusses the importance of parent engagement and adherence, which is essential to the success of PT. Chapter four covers the PT literature on social communication deficits in children with ASD. Chapter five provides information on the prevalence, impact, and predisposing factors for disruptive behavior in children with ASD. Chapter six discusses PT for sleep disturbances most commonly observed in children with ASD. Chapter seven describes PT for children with food selectivity. Chapter eight describes the challenges of bowel and bladder training in children with ASD. Chapter nine presents descriptions and possible motivations of wandering and bolting from caregivers and thoroughly discusses an assessment of this class of behaviors. Chapter ten offers a summary and recommendations for future directions for PT in ASD."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved).